2011
DOI: 10.1007/s10143-010-0301-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgery and elderly: analysis through the years

Abstract: The aging of the population in westernized countries constitutes an important issue for the health systems struggling with limited resources and increasing costs. Morbidity and mortality rates reported for neurosurgical procedures in the elderly vary widely. The lack of data on risk benefit ratios may result in challenging clinical decisions in this expanding group of patients. The aim of this paper is to analyze the elderly patients cohort undergoing neurosurgical procedures and any trend variations over time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…While elderly patients were traditionally categorized as high-risk surgical candidates, remarkable advances in neuroanesthesia, neuromonitoring, and neurocritical care have afforded neurosurgeons the opportunity to successfully perform complex neurosurgical procedures on the elderly, both on an elective and emergency basis. 7 A steady rise in the number of complex neurosurgical procedures in the elderly has been accompanied by a decline in complication rates as evidenced by morbidity and mortality rates that are lower than ever before. An analysis of several reports on outcomes after neurosurgical procedures in the elderly has revealed that advanced age can no longer be used as an absolute contraindication to any neurosurgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While elderly patients were traditionally categorized as high-risk surgical candidates, remarkable advances in neuroanesthesia, neuromonitoring, and neurocritical care have afforded neurosurgeons the opportunity to successfully perform complex neurosurgical procedures on the elderly, both on an elective and emergency basis. 7 A steady rise in the number of complex neurosurgical procedures in the elderly has been accompanied by a decline in complication rates as evidenced by morbidity and mortality rates that are lower than ever before. An analysis of several reports on outcomes after neurosurgical procedures in the elderly has revealed that advanced age can no longer be used as an absolute contraindication to any neurosurgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of several reports on outcomes after neurosurgical procedures in the elderly has revealed that advanced age can no longer be used as an absolute contraindication to any neurosurgical intervention. 7 Intracranial bAVMs are uncommon, likely congenital vascular lesions that mostly present with hemorrhage or seizures. With widespread use of imaging technologies, the incidence of bAVMs in the elderly is on the rise.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to compare quality-of-life improvements and the incidence of side effects in the most elderly patients compared to younger populations. As life expectancy is increasing, the elderly and nonagenarian patient populations are growing, and there is an increased need to find suitable treatment options [16].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the amount of postoperative complications after neurosurgery in elderly persons after neurosurgical procedures, there is a report from Chibbaro et al who analyzed the number of procedures performed, the length of hospital stay, and mortality within 1 month at a university hospital in Paris over a 25-year period [32]. The number of neurosurgical interventions in elderly patients increased steeply from 1983 to 1985 from 10% of patients treated to 24% in the period of 2003 to 2005.…”
Section: Surgerymentioning
confidence: 99%